2015
DOI: 10.1111/scs.12218
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ decisional control over care: a cross‐national comparison from both the patients’ and nurses’ points of view

Abstract: The disparities between patients' and nurses' perceptions on patients' decisional control over their care should be taken into consideration as a potential cause of patient dissatisfaction with nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…We also know that many of today's nurses are not sufficiently trained in fundamental care delivery (MacMillan, ) or how to effectively involve patients in their own care (Huisman‐de Waal, Feo, Vermeulen, & Heinen, ). Although nurses stress the importance of person‐centred care where patients can participate (Bolster & Manias, ; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, ), difficulties are apparent from research demonstrating that nurses overestimate the patient‐centredness of their care, as compared to the patients’ experiences (Papastavrou et al, ; Suhonen et al, ). In a study by Jangland, Teodorsson, Molander, and Muntlin Athlin () on the patients’ perspective of care delivery in surgical hospital wards, it was found that the high‐tempo culture leads to patients not receiving optimal physical or emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…We also know that many of today's nurses are not sufficiently trained in fundamental care delivery (MacMillan, ) or how to effectively involve patients in their own care (Huisman‐de Waal, Feo, Vermeulen, & Heinen, ). Although nurses stress the importance of person‐centred care where patients can participate (Bolster & Manias, ; Tobiano, Bucknall, Marshall, Guinane, & Chaboyer, ), difficulties are apparent from research demonstrating that nurses overestimate the patient‐centredness of their care, as compared to the patients’ experiences (Papastavrou et al, ; Suhonen et al, ). In a study by Jangland, Teodorsson, Molander, and Muntlin Athlin () on the patients’ perspective of care delivery in surgical hospital wards, it was found that the high‐tempo culture leads to patients not receiving optimal physical or emotional support.…”
Section: Introductionmentioning
confidence: 99%
“…3 The patient is a specialist in his/herself and a valuable resource, but they do not always feel like an equal partner in their own healthcare. 4 They are entitled to, and responsible for, decisions that concern their own lives. The nurse can both facilitate the healing process and support the patient in increasing the feeling of well-being that can lead to an improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…2010; Papastavrou et al, 2016). The concept of participation needs to be understood in specific clinical and interactive settings (Kvangarsnes, Torheim, Hole, & Öhlund, 2013).…”
mentioning
confidence: 99%